Money and modernization in early modern England - Nuno Palma (European Historical Economics Society (EHES), 2019)
Classic accounts of the English industrial revolution present a long period of stagnation followed by a fast take-off. However, recent findings of slow but steady per capita economic growth suggest that this is a historically inaccurate portrait of early modern England. This growth pattern was in part driven by specialization and structural change accompanied by an increase in market participation at both the intensive and extensive levels. These, I argue, were supported by the gradual increase in money supply made possible by the importation of precious metals from America. They allowed for a substantial increase in the monetization and liquidity levels of the economy, hence decreasing transaction costs, increasing market thickness, changing the relative incentive for participating in the market, and allowing agglomeration economies to arise. By making trade with Asia possible, precious metals also induced demand for new desirable goods, which in turn encouraged market participation. Finally, the increased monetization and market participation made tax collection easier. This helped the government to build up fiscal capacity and as a consequence to provide for public goods. The structural change and increased market participation that ensued paved the way to modernization.
Keywords: E10; E40; E50; N13; N33; O40; 330; Origins and persistence of modern economic growth; the industrious; industrial and financial revolutions; early modern monetary injections; the great divergence; the little divergence; state-formation; provision of public goods